Sistem Penunjang Keputusan Pemilihan Supplier Terbaik Dengan Metode Analythical Hierarchy Process Pada PT. Konten Indomedia Pratama - Rahma Putri Rizqika; Eva Zuraidah (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2022)
Decision making is basically a form of choosing from a variety of alternatives that may be chosen. Before choosing these alternatives, accurate data is needed for making a decision. If the data entered is inaccurate, the calculation process can result in inappropriate results so that the resulting alternative decision is inaccurate and precise. For a good supplier selection process, a system is needed, so that the selected results are more accurate and precise. The system used is the analytical hierarchy process (AHP) method. Data was collected by means of interviews, observations and literature studies. From these results, the ranking values ??for suppliers are obtained, including: Doungguan Ageless Health Industrial Co.,Ltd ranks 1st with a value of (20.9%), Mediatech.id ranks 2nd with a value of (17.3%) , Huizhou Xiao'ou Technologhy Co., Ltd is in 3rd place with a score of (14%), Purelizer Official Shop is in 4th place with a score of 10.3%, Healicom Medical Equipment Co.,Ltd is in 5th place with a score of (8.60%), Beiqi Industry Development Co.,Ltd ranks 6th with a value of 7.8%, OULI Group (HK) LIMITIED ranks 7th with a value of (6.1%), Medsinglong Global Group Co.,Ltd ranks 8th with a score of (5.8%), P Hangzhou Clongene Biotech Co.,Ltd Hangzhou Clongene Biotech Co.,Ltd ranks 9th with a value of 5.10% and the last Shenzhen UV Green Technology Co., Ltd ranked 10th with a value ( 4.1%). Data processing is carried out using one of the MCDM (Multi Criteria Decision Making) methods, namely the Analytical Hierarchy Process (AHP) method, with the result that the supplier Doungguan Ageless Health Industrial Co., Ltd. was determined as the best supplier.